Determinan Promosi Online dan Dampaknya terhadap Keputusan Pembelian - Hartanti Nugrahaningsih (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
This research aims at